Pars Plana Ahmed Valve Implantation for Vitrectomized Eyes With Refractory Glaucoma - Xiang, Xiaoli; Xiao, Pan; Yu, Jingjing; Cao, Yihong; Jiang, Tingwang; Huang, Zhengru (Frontiers in Medicine, 2022)
This study aimed to analyze the surgical outcomes of pars plana Ahmed valve implantation in vitrectomized eyes with refractory glaucoma. We performed a retrospective case review of consecutive patients with refractory glaucoma after undergoing pars plana vitrectomy who underwent pars plana Ahmed valve implantation between July 2019 and December 2020 at the glaucoma unit of the Affiliated Changshu Hospital of Xuzhou Medical University (Changshu, China). All the patients were followed up for ≥ 12 months postoperatively. We recorded pre- to postoperative changes in best-corrected visual acuity (BCVA), intraocular pressure (IOP), number of anti-glaucoma medication, corneal endothelial count, and surgical complications, if any. There was a significant improvement in the median BCVA from 2.30 (0.87, 2.30) logMAR preoperatively to 1.70 (0.70, 2.30) logMAR at discharge and 1.0 (0.52,1.85) at final examination (p= 0.011, p = 0.001). Compared with the preoperative IOP level, there was a significant decrease in the postoperative IOP at each postoperative time point (p < 0.001). There was a significant reduction in the median number of anti-glaucoma drugs (including postoperative ocular massage), from 3.00 (2.00, 3.00) preoperatively to 0.00 (0.00, 1.00) at the last follow-up postoperative examination (p < 0.001). A 29-year-old woman with proliferative diabetic retinopathy who underwent surgical treatment at 5 months postoperatively for fibrous wrapping formed around the plate of the Ahmed valve showed an IOP of 14 mmHg at the last follow-up. Our findings indicated that pars plana Ahmed valve implantation can be safely performed for managing vitrectomized eyes with refractory glaucoma.